Study on Mechanism of Roundness Improvement by the Internal Magnetic Abrasive Finishing Process Using Magnetic Machining Tool - Jiangnan Liu; Yanhua Zou (Machines, 2022)
An internal magnetic abrasive finishing process using a magnetic machining tool was proposed for finishing the internal surface of the thick tubes. It has been proved that this process is effective for finishing thick tubes, and it can improve the roundness while improving the roughness. However, the mechanism of improving the roundness is not clear, so it is necessary to study it theoretically. In this research, firstly, the roundness curve expression was derived using the principle of roundness measurement by the assumed center method, and the expression of roundness curve expanded by Fourier series was obtained. The influencing factors of roundness improvement were then analyzed. Secondly, the experiments were carried out on SUS304 stainless steel tubes. By confirming the mechanism analysis results and the experimental results, it was concluded that the internal magnetic abrasive finishing process using the magnetic machining tool was effective for improving the roundness of the thick tubes whose thickness is from 10 mm to 30 mm. As the thickness of the tube increased, the improvement in roundness decreased.